A Randomized Trial of Home Blood-Pressure Reduction by Alcohol Guidance During Outpatient Visits: OSAKE Study. (23rd May 2021) - Kabayama, Mai; Akagi, Yuya; Wada, Naoko; Higuchi, Atsuko; Tamatani, Michio; Tomita, Jun; Nakata, Yukako; Takiuchi, Shin; Yamamoto, Koichi; Sugimoto, Ken; Shintani, Ayumi; Rakugi, Hiromi; et al.
Abstract: Background: To evaluate the effectiveness of the nurse-led alcohol guidance to control home blood pressure (HBP) in the morning among male patients with hypertension during outpatient visits. Methods: We enrolled 53 male patients with an HBP of ≥135/85 mm Hg with excessive drinking (alcohol ≥210 g/week or ≥60 g/day habitually) among outpatients in a randomized trial. Patients were assigned to a nurse-led alcohol guidance intervention or to the control. The primary outcomes were the mean HBP of 5 consecutive days at 6 months and alcohol consumption. Results: Twenty-eight and 25 patients were randomized to intervention and control groups, respectively (mean age; 62.7 years old and 64.5, respectively). At baseline, the groups were well balanced across most characteristics. At 6 months, the mean HBP was 131/82 mm Hg in the intervention group vs. 145/87 mm Hg in the control group (SBP <0.001, DBP = 0.09). An HBP level of less than 135/85 mm Hg was achieved among 55.6% of the participants in the intervention group vs. 16.7% in the control group (P = 0.004). The alcohol consumption at 6 months was 256 ± 206 g/w vs. 413 ± 260 g/w, respectively ( P = 0.020). Conclusions: We confirmed the effectiveness of the nurse-led alcohol guidance to control the HBP in male patients with hypertension during outpatient visits. Public trials registry number: UMIN000017454 (UMIN Clinical Trials Registry).